The Process of Creating the Syaga Sinatriya Dance by Mochamad Rafli Wisnu Triwijaya and Virdha Annora Zavira - Wisnu Triwijaya, Mochamad Rafli; suryandoko, welly (Solah, 2026)
The Syaga Sinatrya dance was created by two choreographers, Mochamad Rafli Wisnu Triwijaya and Virdha Annora Zavira, and won first place in the 2024 Bengkulu University National Student Art Week (PEKSEMA) creative dance competition. This work was inspired by the figures of Raden Arjuna and Dewi Wara Srikandi, who are known for their warrior spirit. Thus, the meaning of “Syaga Sinatrya” is the alertness of a soldier who is always self-aware in order to prepare both his mind and body for the battlefield. This report aims to describe the dance creation process carried out by the choreographer in the dance Syaga Sinatrya. It uses the creative process method (Hadi, 2016), which classifies four stages, namely exploration, improvisation, composition (formation), and evaluation. The Syaga Sinatrya dance represents the alertness of soldiers in fighting the conflicts within their souls and bodies. It is performed by three female dancers and two male dancers, in an East Javanese style, specifically that of the Arek ethnic group. The makeup uses stage makeup, kutungan costumes and shorts, and other supporting components dominated by red and gold colors, symbolizing strength and spirit. The dance props use modified cundrik gendewa, performed on a proscenium stage, supported by Fresnel lighting and LED par lights. The dance accompaniment uses recordings of titilaras pelog gamelan instruments and modern music. Keywords: Creation Process, Presentation Process, Creative Dance, Syaga Sinatrya